Kajian gen Amely Gajah Sumatra (Elephas maximus sumatranus) - Zein, Moch Syamsul Arifin; Sulandari, Sri (Perhimpunan Biologi Indonesia, 2016)
Sumatran elephants (Elephas maximus sumatranus) is endemic of Asian elephants in Indonesia, an endangered animal andlisted on Appendix I of CITES. Therefore, information on the status and distribution of the population of Sumatranelephants, including the distribution of genetic diversity is necessary to facilitate the development of adequate conservationand management strategies. The purpose of this research was to use Amely gene to trace paternal lineage of Sumatranelephants based on Y chromosome variation. A total of 22 blood samples of male Sumatran elephants were collected inSumatra (Way Kambas , Seblat, Bentayan, Sugihan, dan Bukit Serelo Lahat). We amplified intronic regions of the Ylinkedgene (Amely) using published primer sequences (Amely-R2 and Amely-F2) and sequenced. Sequences generatedfrom this study, aligned with reference sequences available in the GenBank, namely Elephas maximus (AY823325.1),Loxodonta Africana (AY 823320.1; AY 823321.1), Loxodonta cyclotis (AY823322.1; AY8233223.1, AY 823324.1).Neighbour Joining tree of Sumatran elephants was performed using MEGA version 5.2.2. The analysis results of 22-maleSumatran elephants, indicating that no diversity (no variation) of the Y chromosome obtained among the population ofSumatran elephants. Sumatran and Asian elephants have the same haplotypes. Further results confirmed that the savannaelephants (Loxodonta africana ) and the forest elephants (Loxodonta cyclotis ) formed two (2) separate clades, which showstwo different species. Results obtained in this study may help to design future conservation programs for the species.Keywords: Sumatran elephant, Amely gene, Y chromosome, Genbank, haplotype